2002
DOI: 10.1002/bies.10085
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the regionalisation of the developing vertebrate central nervous system

Abstract: During embryonic development, a number of tissues are patterned by their subdivision into domains with distinct regional identity. An important question is how sharp interfaces are established and maintained between adjacent domains despite the potential for scrambling due to cell intermingling during tissue growth. Two mechanisms have been found to underlie the maintenance of sharp interfaces: the specific restriction of cell mixing across boundaries, or the switching of identity of cells that cross between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…However, delayed induction of proto-rhombomere domains in fgf8-compromised embryos does not affect the eventual development of rhombomere compartments with sharply specified boundaries. This result is consistent with what is known about the delineation of sharp boundaries between rhombomeres, a process that occurs throughout early somitogenesis stages, when cells retain plasticity in their ability to contribute to different rhombomeres (reviewed in Pasini and Wilkinson, 2002).…”
supporting
confidence: 89%
“…However, delayed induction of proto-rhombomere domains in fgf8-compromised embryos does not affect the eventual development of rhombomere compartments with sharply specified boundaries. This result is consistent with what is known about the delineation of sharp boundaries between rhombomeres, a process that occurs throughout early somitogenesis stages, when cells retain plasticity in their ability to contribute to different rhombomeres (reviewed in Pasini and Wilkinson, 2002).…”
supporting
confidence: 89%
“…2 D and E) (30). Several studies of the developing brain have demonstrated that similar sets of genes are used to establish a particular anatomical region and to maintain the cell-cell relationships of the differentiated region (31). Thus, it may be that the roles of these genes in adulthood are similar to their roles during development.…”
Section: Discussionmentioning
confidence: 99%
“…During neural vertebrate development, it has been reported to be essential for the segmentation of the hindbrain and the formation of the zona limitans intrathalamica (Lewis, 1998, Pasini and Wilkinson, 2002, Kiecker and Lumsden, 2005. Although the exact mechanism by which adjacent regional domains acquire distinct properties in vertebrates is less clear, the underlying model extracted from Drosophila predicts that Notch pathway is differentially activated by the different expression of Delta and Serrate ligands and the modulator Fringe in adjacent territories.…”
Section: Principles Of the Notch Signaling Pathwaymentioning
confidence: 99%